Formulation of Soygurt Mung Bean with Date Juice as Adjuvant Therapy for Diabetes Mellitus - Jannah, Miftakhul; Rahardjo, Setyo Sri; Febrinasari, Ratih Puspita (Nusantara Science and Technology Proceedings, 2024)
One innovative nutritional therapy approach for diabetic mellitus (DM) is modulating the gut microbiota by administering probiotics. Soygurt is a probiotic functional food made from fermenting soy milk with lactic acid bacteria (LAB), which includes bioactive peptides and antioxidants. The use of soybean, mungbean, and date juice as sweeteners is expected to increase the product's physicochemical quality as well as the presence of lactic acid bacteria, maximizing its benefits as a functional meal for DM. This study was an experiment that used a completely randomized design with three treatment formulas comparisons of soybeans and mungbean's (% : %) as follows F1 (25:75), F2 (50:50), and F3 (75:25). Protein content was determined using the biuret method, fat content was identified using the mojonieur method, the reduced sugar content was analyzed using the Nelson Smogyi method, crude fiber content was identified using the gravimetric, and LAB were determined using the Total Plate Count (TPC). The best formula was continued for clinical trials on animals. The result of F3 produced protein of 5.46%, fat of 2.36%, reduced sugar of 4.66%, crude fiber of 3.81%, and a pH of 4.139. The lactic acid bacteria (LAB) count in F1 was 1.9 x 108 CFU/mL. It concluded that soygurt mung bean with date juice can potentially control blood glucose levels due to its high protein and low-fat content.